The Annals of Quintus Ennius and the Italic Tradition - Fisher, Jay, 1969- (Book collections on Project MUSE., 2014)
"Jay Fisher argues that Ennius does not simply translate Homeric models into Latin, but blends Greek poetic models with Italic diction to produce a poetic hybrid. Fisher's investigation uncovers a poem that blends foreign and familiar cultural elements in order to generate layers of meaning for his Roman audience. Fisher combines modern linguistic methodologies with traditional philology to uncover the influence of the language of Roman ritual, kinship, and military culture on the Annals"--